2004
DOI: 10.1103/physrevd.70.121302
|View full text |Cite
|
Sign up to set email alerts
|

Vector perturbations in a contracting Universe

Abstract: In this note we show that vector perturbations exhibit growing mode solutions in a contracting Universe, such as the contracting phase of the Pre Big Bang or the Cyclic/Ekpyrotic models of the Universe. This is not a gauge artifact and will in general lead to the breakdown of perturbation theory -a severe problem that has to be addressed in any bouncing model. We also comment on the possibility of explaining, by means of primordial vector perturbations, the existence of the observed large scale magnetic fields… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(92 citation statements)
references
References 29 publications
1
90
0
1
Order By: Relevance
“…However, if we start with a universe initially devoid of vector perturbations and only scalars are present, this hurdle can be overcome as scalars do not source vector perturbations [245]. This is possible as vector perturbations, not being dynamical in this context, do not need to have non-vanishing initial conditions coming from, e.g.…”
Section: B Growth Of Quantum Induced Anisotropymentioning
confidence: 99%
See 1 more Smart Citation
“…However, if we start with a universe initially devoid of vector perturbations and only scalars are present, this hurdle can be overcome as scalars do not source vector perturbations [245]. This is possible as vector perturbations, not being dynamical in this context, do not need to have non-vanishing initial conditions coming from, e.g.…”
Section: B Growth Of Quantum Induced Anisotropymentioning
confidence: 99%
“…This work superseded that of [170] which set up the building blocks to obtain scale-invariant entropy perturbations within the ekpyrotic scenario via non-minimally coupled massless scalar fields. There, it was suggested that the entropy perturbation could be converted into curvature perturbations by means of a curvaton, as done in [169], or modulated (p)reheating [245]. Non-Gaussianities for the model in [169] where computed in [171], see the non-minimal entropic mechanism in Table II.…”
Section: F Nonsingular Bounces Via a Galileonmentioning
confidence: 99%
“…Note that vector and tensor perturbations are important (see e.g. [47]) in topological defects models of structure formation and in bouncing cosmologies [48].…”
Section: Classifying Fluctuationsmentioning
confidence: 99%
“…Vector perturbations (VP) have recently been studied in the context of bouncing cosmologies, due to their growing nature in a contracting Universe [44,45]. However, if the fluid is stiff enough, VP will also grow in an expanding Universe (as was first pointed out in [46]).…”
Section: Vector Perturbations In Thementioning
confidence: 99%
“…If we assume for simplicity π i = 0 (no anisotropic stress), the equations of motion for each Fourier mode V k and S k are solved by [44] …”
Section: Vector Perturbations In Thementioning
confidence: 99%